Should this event be notified to the World Health Organization? reliability of the international health regulations notification assessment process - Thomas Haustein; Helge Hollmeyer; Max Hardiman; Stephan Harbarth; Didier Pittet (Bulletin of the World Health Organization)
OBJECTIVE: To investigate the reliability of the public health event notification assessment process under the International Health Regulations (2005) (IHR). METHODS: In 2009, 193 National IHR Focal Points (NFPs) were invited to use the decision instrument in Annex 2 of the IHR to determine whether 10 fictitious public health events should be notified to WHO. Each event's notifiability was assessed independently by an expert panel. The degree of consensus among NFPs and of concordance between NFPs and the expert panel was considered high when more than 70% agreed on a response. FINDINGS: Overall, 74% of NFPs responded. The median degree of consensus among NFPs on notification decisions was 78%. It was high for the six events considered notifiable by the majority (median: 80%; range: 76-91) but low for the remaining four (median: 55%; range: 54-60). The degree of concordance between NFPs and the expert panel was high for the five events deemed notifiable by the panel (median: 82%; range: 76-91) but low (median: 51%; range: 42-60) for those not considered notifiable. The NFPs identified notifiable events with greater sensitivity than specificity (P < 0.001). CONCLUSION: When used by NFPs, the notification assessment process in Annex 2 of the IHR was sensitive in identifying public health events that were considered notifiable by an expert panel, but only moderately specific. The reliability of the assessments could be increased by expanding guidance on the use of the decision instrument and by including more specific criteria for assessing events and clearer definitions of terms.